The effect of changing the nano size on the absorption coefficient and the energy gap of crushed Na Cl samples (Eurasian Journal of Physics,Chemistry and Mathematics, 2022)
Nanoscience represents one of the most powerful tools for controlling and changing the physical properties of matter. In this work, eight NaCl samples were prepared and crushed into different micro sizes. Their nano sizes were examined using an X-ray diffraction technique. The examination showed that the nana crystal size increases upon increasing the micro crunch size. The ultra violet-visible spectrometer results indicate that the absorption coefficient increases and the energy gap decreases when the crystal nano size and the crush size increase